Guidance of young children - Marion, Marian (Merrill, 1995)
Based on her belief that adults need to have realistic expectations of children, Marian Marion's Guidance of Young Children emphasizes understanding young children's development, using a developmentally appropriate approach to guidance, and thinking critically in making wise guidance decisions. social-emotional development, guiding children during routines and transitions, revised presentation on child development, methods of observing, expanded and revised coverage on theories, theoretical application to constructing physical environments For Early Childhood Educators teaching courses in Guidance in Early Childhood Education or Behavior Management of Young Children.